Integrating Developmental and Educational Psychology for Student Well-Being and Motivation: A Systematic Literature Review (2019–2024) - Sultan Aprilianno Lautan Ardin; Basudewa Sinatria; Ahmad Irfan (P3I UMSurabaya, 2025)
This article presents a literature-based review exploring how developmental and educational psychology contribute to educational enhancement and innovation. Using a systematic literature study of 15 international and 5 national journals published between 2019 and 2024, the paper analyzes major themes including cognitive and socio-emotional development, motivation, curriculum design, inclusive education, and student well-being. Findings reveal that integrating psychological and developmental frameworks into teaching practice enhances learning motivation, student engagement, and mental health, while supporting a more holistic approach to education. However, challenges remain teachers’ limited understanding of developmental theory, lack of resources, and the gap between theory and practice. The article concludes by emphasizing the importance of professional teacher training, culturally adaptive policies, and mixed method research to validate developmental psychological interventions in various educational contexts.